Evidence for the aetiology of injuries in Australian football. Issue 6 (1st December 2001) - Norton, K; Schwerdt, S; Lange, K
Abstract : Objectives —To determine in Australian football ( a ) the influence of ground hardness and playing grade (level) on game speed and structure, and ( b ) player movement patterns throughout the game and across levels. Methods —The design consisted of several studies. Seventeen games played on grounds of different hardness in 2000 were used to determine game speed and structure. Four first grade and four second grade grand final games (1994, 1996, 1997, 1999) were used to determine the game speed and structure on the same ground but at different levels. Fifty one players (44 first grade and seven second grade) were used to measure movement patterns within games and across levels during the 2000 season. Results —There was a significant relation between ground hardness and game speed, which could lead to higher injury rates when the ground is harder. There was a 6.7% difference in game speed between the first and second grade levels reflecting differences in injury incidence. The first grade games were also characterised by a greater number of shorter, high intensity play periods and longer stop periods than the second grade games. Midfield players in the first grade games covered about 24% greater distance than their second grade counterparts, and there was a significant difference in their playing speeds. Conclusions —Over the past 40 years, the game speed in the top level of Australian football has approximately doubled. Over the same time, the number of collisions and the estimated injury incidence have also doubled. This study provides additional support to the suggestion that these variables are strongly linked. Factors such as ground hardness, playing level, and time during the game influence game speed and are therefore important in injury development in Australian football.